PENGARUH ANALISIS LAPORAN DALAM MENILAI KINERJA KEUANGAN PT.INDOFOOD SUKSES MAKMUR Tbk - Tri Sukma Ayu Purba; Lusiana F Rajagukguk; Vitaloka Manik; Hamonangan Siallagan (Jurnal Publikasi Manajemen Informatika, 2025)
Financial report analysis is the process of breaking down data in financial reports into separate components, studying the relationships between components and getting a comprehensive picture. Business competition requires every company to be able to show the best performance from every business it runs. Financial performance measures can work well when applied to all business entities where operating investment and financing are collectively controlled by management. This analysis illustrates whether the company's performance is experiencing good growth or not through the method of calculating financial ratios by comparing financial reports for 2 periods. The preparation of financial reports must refer to generally accepted financial accounting principles. The aim of the research is to determine the financial performance of PT. Indofood Sukses Makmur Tbk for the 2020 and 2021 periods using liquidity and profitability methods. The results of the discussion showed that the financial performance of PT. Indofood Sukses Makmur Tbk is seen with fluctuating ratios every year, this is due to increases or decreases in financial report items, for example sales, inventory, profits, etc.